Leaking stoppage framework material as well as preparation method and application thereof

By forming a composite film of polyvinyl alcohol and inorganic particles on the surface of the elastic sponge, the problem of leakage plugging materials failing in high temperature and oil-based drilling fluid is solved, good hydrophobicity and oil resistance are achieved, and the leakage plugging effect is improved. Repeated missed.

CN119144305AActive Publication Date: 2024-12-17CHINA PETROLEUM & CHEMICAL CORP +3
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310714467.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-15
Publication Date
2024-12-17
Estimated Expiration
2043-06-15

AI Technical Summary

Technical Problem

The existing leak-blocking skeleton materials fail in high temperature and oil-based drilling fluid, which cannot effectively solve the problem of malignant cave leakage. Moreover, the temperature resistance of conventional materials is poor, which can easily lead to repeated leakage.

Method used

By coating polyvinyl alcohol and inorganic particles on the surface of the elastic material sponge to form a composite film, the hydrophobicity, mild and oil resistance of the material is improved, and a mesh structure is formed to enhance the leakage plugging effect.

Benefits of technology

Maintain elasticity in high-temperature and oil-based drilling fluid, effectively disperse and improve the leakage plugging effect of leakage plugging materials, avoid repeated leakage. It is suitable for various types of leakage, especially for joint hole type leakage, which has excellent leakage plugging effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119144305A_ABST
    Figure CN119144305A_ABST
Patent Text Reader

Abstract

The invention discloses a leaking stoppage framework material as well as a preparation method and application thereof, and belongs to the technical field of petroleum drilling. The invention provides a leaking stoppage framework material. The leaking stoppage framework material is prepared by coating the surface of an elastic material with polyvinyl alcohol and inorganic matter particles, the elastic material is selected from at least one of sponge, elastic graphite and rubber, according to the leaking stoppage framework material, the elastic material is modified, the hydrophobicity, temperature resistance and oil resistance of the raw material of the elastic material are improved, and the leaking stoppage framework material is good in dispersity in oil-based drilling fluid, not prone to the swelling problem, good in elasticity and good in matching performance with cracks, and the leaking stoppage framework material can be used for leaking stoppage of the oil-based drilling fluid. The deep part of the crack is facilitated; meanwhile, the plugging framework material can restore the shape after entering the crack, bridging and net forming are facilitated, the plugging framework material has a good plugging effect on various types of leakage, the plugging success rate can be well increased, repeated leakage is avoided, and the plugging framework material has a good plugging effect on fracture-cavity type leakage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil drilling, and in particular to a leak-proof skeleton material and a preparation method and application thereof. Background Art

[0002] Well leakage is the phenomenon that various working fluids leak into the formation under the action of pressure difference during various downhole operations such as drilling, cementing completion, testing or well repair. Once well leakage occurs, it will not only delay drilling time, lose drilling fluid, damage oil and gas layers, interfere with geological logging work, increase drilling costs, but also easily cause a series of complex situations such as drill sticking, blowout, well collapse, and even lead to the scrapping of the wellbore, causing huge economic losses.

[0003] With the further understanding of the causes of different well leakage, the research and development of plugging skeleton materials is also constantly improving. When a well leak occurs, the compound ratio of granular, flaky and fibrous plugging skeleton materials is generally adjusted according to the different pore sizes and positions of the leakage layer, and appropriate inert materials are added to complement them to enhance the plugging effect. Commonly used granular plugging skeleton materials include walnut shells, rubber particles, diatomaceous earth, asphalt, etc.; fibrous materials include sawdust, cotton fiber, flax fiber, etc.; sheet materials include mica flakes, rice husks, etc. During the drilling process, artificial cracks caused by fast drilling speed or fast drilling can be plugged by using the non-solidified characteristics of soft and hard plugging skeleton materials to form non-flowing viscous substances. Such materials mainly include diesel bentonite slurry, shear thickening liquid, barite plug and lime milk. The above types of plugging skeleton materials can solve partial leakage and loss-return leakage caused by pores and cracks, but some complex leakage cannot be solved well. Therefore, various new plugging agents such as chemical plugging agents, high water loss plugging agents, mixed plugging slurries, etc. have emerged, providing effective means to deal with various types of well leakage and improve the success rate of well leakage treatment.

[0004] With the continuous advancement of technology, various targeted plugging skeleton materials have been developed, including high water loss plugging skeleton materials, chemical plugging skeleton materials, mixed plugging thick slurry, etc. After the high water loss plugging skeleton material slurry enters the leakage layer, it quickly loses water to form a filter cake under the pressure difference generated by the drilling fluid column pressure and the bottom pressure, plugging the leakage channel. This type of material mainly includes permeable materials, fibrous materials, diatomaceous earth and porous inert materials; chemical plugging skeleton materials use the static force, intermolecular force and chemical bond force of polymers on the interface to make the compounds form adhesion at the interface to play a plugging role. This type of material includes gel plugging agent, resin plugging agent and expansion plugging agent; mixed plugging thick slurry is mainly based on special cement and mixed cement thick slurry, and different admixtures are added to improve the early strength and stability of cement stone, so that it has a higher pressure bearing capacity. These types of plugging skeleton materials can play a good plugging role for permeable leakage and fracture leakage. However, with the improvement of drilling technology requirements, vicious leakage such as cave leakage often occurs, and these conventional plugging skeleton materials cannot effectively play a plugging role.

[0005] At present, the commonly used plugging skeleton materials in plugging construction are often bridging plugging skeleton materials and chemical gel plugging skeleton materials. Chemical plugging mainly plays a plugging role through the chemical reaction of polymers, including cross-linking reaction, curing reaction and other methods. Chemical plugging has a good plugging effect on malignant leakage, but the chemical plugging reaction is more intense, the construction is complex and the risk is higher. The bridging plugging skeleton material has a simple construction process and low cost. It is the most commonly used on site, but some materials have poor temperature resistance and are prone to decomposition and failure at high temperatures, resulting in repeated leakage of the leaking layer. At the same time, these materials have problems such as sealing the door and cannot be soaked for a long time, and the plugging effect is sometimes not ideal.

[0006] In the past two decades, researchers have discovered a variety of methods for preparing ultra-thin films through in-depth exploration. In particular, there has been great progress in the field of layer-by-layer self-assembly, which is due to the fact that this method has very good effects in the innovative design and application of ultra-thin films with special functional properties. For example, Chinese patent CN101085880A proposes a nano-layered calcium carbonate bionic composite material, which is a low-molecular-weight organic matter participating in the reaction process of calcium chloride and sodium carbonate, guiding calcite to form a nano-thin layer structure, and then making the layered structure oriented to assemble a multilayer structure of nano-thin layers. These studies have played an important role in promoting the biomimetic synthesis of biomineralized materials, but have not yet grown into bionic materials with natural calcium carbonate structures, or the methods and material performance need to be further improved.

[0007] Some researchers use sponge as a skeleton material with high crack matching properties. For example, Chinese patent CN103923627A discloses an oil and gas well drilling pressure plugging agent, which is composed of a mixture of elastic sponge fiber, oil well cement, ground slag, calcic clay, mica powder and clean water, and can be used for oil and gas well drilling pressure plugging.

[0008] At present, sponge materials are prone to swelling in oil-based drilling fluids, which leads to loss of elasticity and greatly reduces the plugging effect. Therefore, it is necessary to modify the sponge to improve its hydrophobicity and temperature and oil resistance. Summary of the invention

[0009] In view of the deficiencies in the prior art, the present invention provides a leak-proof skeleton material and a preparation method and application thereof. The leak-proof skeleton material improves the hydrophobicity, temperature resistance and oil resistance of the original elastic sponge material by modifying the elastic material sponge. The leak-proof skeleton material has good dispersibility in oil-based drilling fluid, is not prone to swelling problems, has good elasticity, has good matching with cracks, and is conducive to deep crack penetration. At the same time, the leak-proof skeleton material can restore its shape after entering the crack, which is conducive to the implementation of bridging and networking. It has a good leak-proof effect on various types of leaks, can better improve the leak-proof success rate, avoid the occurrence of repeated leaks, and has a good leak-proof effect on fracture-hole type leaks.

[0010] In order to solve the above technical problems, the first aspect of the present invention provides a plugging skeleton material, which includes an elastic material and a deposited film coated on the surface of the elastic material; the raw materials for preparing the deposited film include polyvinyl alcohol, inorganic particles and an optional cross-linking agent; the elastic material is selected from at least one of sponge, elastic graphite and rubber.

[0011] According to some embodiments of the present invention, taking the total mass of the leak-proof skeleton material as 100%,

[0012] The mass percentage of elastic material is 89% to 95.7%.

[0013] The mass percentage of polyvinyl alcohol is 2.2% to 5.6%;

[0014] The mass percentage of inorganic particles is 2.1% to 4.4%;

[0015] The mass percentage of the cross-linking agent is 0% to 1%.

[0016] According to some embodiments of the present invention, the cross-linking agent is selected from at least one of glutaraldehyde and boric acid.

[0017] According to some embodiments of the present invention, the average particle size of the elastic material is 1 mm to 5 mm.

[0018] According to some embodiments of the present invention, the sponge is a polyurethane sponge or a polyether polyol sponge, and the sponge has mesh pores.

[0019] According to some embodiments of the present invention, the average particle size of the inorganic particles is 0.05 μm to 1 μm, for example 0.05 μm, 0.1 μm, 0.5 μm, 0.8 μm, 1 μm; preferably, the inorganic particles are selected from at least one of montmorillonite, nano-calcium carbonate, and sepiolite.

[0020] According to some embodiments of the present invention, the pore size of the sponge is 10 ppi to 40 ppi, preferably 30 ppi, the open porosity is 95% to 96%, preferably 96%, and the density is 21 kg / cm 3 ~22kg / cm 3 , preferably 22kg / cm 3 .

[0021] According to some embodiments of the present invention, the mass retention rate of the leak-proof skeleton material is 91.8% to 96.9%, the tensile strength is 0.59 MPa to 5.56 MPa, and the tensile strength retention rate is 75.8% to 92.4%.

[0022] The second aspect of the present invention provides a method for preparing the above-mentioned leak-proof skeleton material, comprising the following steps:

[0023] 1) coating a solution I containing polyvinyl alcohol and a solution II containing inorganic particles on the surface of the elastic material in sequence, or coating a mixed solution containing inorganic particles and polyvinyl alcohol on the surface of the elastic material;

[0024] 2) After repeating step 1) for 50 to 200 times, the coated elastic material is dried to obtain the leak-proof skeleton material.

[0025] According to some embodiments of the present invention, in step 1), in the solution I containing polyvinyl alcohol, the solvent I is selected from water; preferably, the content of polyvinyl alcohol in the solution I containing polyvinyl alcohol is 0.5wt% to 1.0wt%, for example, 0.5wt%, 0.8wt%, 0.9wt%, 1wt%.

[0026] According to some embodiments of the present invention, in step 1), in the solution II containing inorganic particles, the solvent II is selected from at least one of water, white oil, and brine; preferably, the brine is selected from a NaCl aqueous solution with a mass concentration of 20%;

[0027] And / or, the content of the inorganic particles in the solution II containing the inorganic particles is 0.1 wt% to 0.5 wt%, for example, 0.1 wt%, 0.2 wt%, 0.5 wt%.

[0028] According to some embodiments of the present invention, in step 2), the drying conditions include: a temperature of 60°C to 80°C, for example, 60°C, 70°C, 80°C; and a time of 2h to 8h, for example, 2h, 3h, 4h, 5h, 6h, 7h, 8h.

[0029] According to some embodiments of the present invention, in step 1), the mixed solution containing inorganic particles and polyvinyl alcohol is a mixed solution of solution I containing polyvinyl alcohol and solution II containing inorganic particles; wherein the total content of inorganic particles and polyvinyl alcohol is 10wt% to 15wt%, for example, 10wt%, 15wt%; and / or, the mass ratio of inorganic particles to polyvinyl alcohol in the mixed solution containing inorganic particles and polyvinyl alcohol is (0.7 to 1): (1.5 to 2), for example, 0.8:1.5, 1:2, 1:1.8, 0.8:1.8.

[0030] According to some embodiments of the present invention, in step 1), the mixed solution containing inorganic particles and polyvinyl alcohol also includes a cross-linking agent; and / or the content of the cross-linking agent in the mixed solution containing inorganic particles and polyvinyl alcohol is 0.1wt% to 1wt%, for example, 0.8wt%, 0.9wt%, 1wt%.

[0031] The crosslinking agent in the present invention can effectively improve the quality and speed of film formation; wherein, the crosslinking between glutaraldehyde and polyvinyl alcohol is an aldol condensation reaction between hydroxyl and aldehyde, wherein the aldehyde first reacts with the hydroxyl to generate hemiacetal, and the hemiacetal then dehydrates and condenses with the hydroxyl to generate ether, thereby ensuring that montmorillonite and polyvinyl alcohol form a network structure under the crosslinking of glutaraldehyde; the mechanism of boric acid crosslinking is that boric acid is hydrolyzed in water to generate B(OH)3, B(OH)4 - , B(OH)4 - It can be dehydrated and esterified with the hydroxyl groups on the polyvinyl alcohol (PVA) chain to generate boric acid esters. Since each boron atom has four esterification reaction functional groups, it can react on different molecular chains, making the PVA molecules cross-linked to form a network structure.

[0032] The third aspect of the present invention provides a plugging skeleton material or the plugging skeleton material prepared by the above preparation method for use in drilling engineering plugging, oil production water plugging and profile control, and drilling fracturing.

[0033] Beneficial effects:

[0034] The plugging skeleton material of the present invention has good hydrophobicity and oil and temperature resistance, will not fail in high temperature and oil-based drilling fluid, can be effectively dispersed in oil-based drilling fluid, is conducive to the preparation of oil-based drilling fluid plugging agent, thereby improving the plugging effect of the plugging material under high temperature of oil-based drilling fluid and avoiding the occurrence of repeated leakage.

[0035] The leak-proof skeleton material of the present invention forms a composite film on the surface of the polyurethane sponge (elastic material). The composite film has hydrophobicity, oil resistance and certain mechanical strength, is easy to disperse in oil-based drilling fluid, and will not affect the rheology of the drilling fluid, thereby solving the problem that conventional leak-proof skeleton materials cannot be dispersed in oil-based drilling fluid, resulting in unsatisfactory leak-proof effect. The reason for the hydrophobicity of the composite film may be that after the introduction of the cross-linking agent, the addition of hydroxyl groups to aldehyde groups reduces the number of hydroxyl groups on the PVA chain, thereby reducing the possibility of hydroxyl groups forming hydrogen bonds with water. Secondly, cross-linking forms a network structure, which limits the activity space of PVA molecules.

[0036] The plugging skeleton material of the present invention is not easy to swell, can maintain elasticity in oil-based drilling fluid, has good compatibility with cracks, and is conducive to deep cracks. At the same time, it can restore its shape after entering the cracks, which is conducive to the implementation of bridging and networking, and has a good plugging effect on various types of leakage. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Contact angle of leak-proof skeleton material. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with the embodiments, but the present invention is not limited by these embodiments.

[0039] In the present invention, the contact angle measuring instrument is purchased from Beijing Harke Testing Instrument Factory, and the model is HARKE-SPCA.

[0040] In the present invention, the high temperature roller heating furnace is purchased from Qingdao Haitong Yuanda Instrument Co., Ltd., and the model is XGRL-4.

[0041] In the present invention, the universal testing machine was purchased from Jiangsu Tianyuan Testing Equipment Co., Ltd., model TY8000.

[0042] In the present invention, the spatula, drying oven and oil bath pot can be any commercially available ones unless otherwise specified.

[0043] In the present invention, the wedge-shaped long fracture plugging experimental device is a conventional experimental device in this field, which is developed by China University of Petroleum (East China).

[0044] In the present invention, the diesel oil is purchased from Shengli Oilfield, and the model is No. 0.

[0045] In the present invention, the montmorillonite is nanomontmorillonite with a purity greater than 98%, purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.

[0046] The degree of polymerization of polyvinyl alcohol in the present invention is 1500, which is purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0047] The pore size of the polyurethane sponge in the present invention is 30ppi, the open porosity is 96%, and the density is 22kg / cm 3 The average particle size of the polyurethane sponge was 5 mm, which was purchased from Shenzhen Lvchuang Environmental Protection Filter Material Co., Ltd.

[0048] In the polyvinyl alcohol solution, montmorillonite solution, sepiolite solution, nano calcium carbonate solution, mixed solution of montmorillonite and polyvinyl alcohol, and polyethyleneimine solution of the present invention, the solvent is water.

[0049] Example 1

[0050] This embodiment provides a leak-proof skeleton material and a preparation method thereof.

[0051] The raw materials for preparing the leak-proof skeleton material are as follows: the mass fraction of polyurethane sponge is 95%, the mass fraction of polyvinyl alcohol is 2.8%, and the mass fraction of montmorillonite is 2.2%.

[0052] A 1wt% polyvinyl alcohol solution and a 0.5wt% montmorillonite solution were prepared respectively, and then the polyvinyl alcohol solution and the montmorillonite solution (montmorillonite particle size 1 μm) were applied to the surface of the polyurethane sponge in sequence using a spatula. After repeating the application operation 120 times, the coated polyurethane sponge was placed in a drying oven at 80°C and dried for 2 hours to obtain the leak-proof skeleton material.

[0053] Example 2

[0054] This embodiment provides a leak-proof skeleton material and a preparation method thereof.

[0055] The raw materials for preparing the leak-proof skeleton material are as follows: the mass fraction of polyurethane sponge is 90%, the mass fraction of polyvinyl alcohol is 5.6%, and the mass fraction of montmorillonite is 4.4%.

[0056] A 0.5wt% polyvinyl alcohol solution and a 0.1wt% montmorillonite solution were prepared respectively, and then the polyvinyl alcohol solution and the montmorillonite solution (montmorillonite particle size 0.05μm) were applied to the surface of the polyurethane sponge in sequence using a spatula. After repeating the application operation 50 times, the coated polyurethane sponge was placed in a drying oven at a temperature of 60°C and dried for 5 hours to obtain the leak-proof skeleton material.

[0057] Example 3

[0058] This embodiment provides a leak-proof skeleton material and a preparation method thereof.

[0059] The raw materials for preparing the leak-proof skeleton material are as follows: the mass fraction of polyurethane sponge is 92.2%, the mass fraction of polyvinyl alcohol is 5.2%, and the mass fraction of montmorillonite is 2.6%.

[0060] A 0.8wt% polyvinyl alcohol solution and a 0.2wt% montmorillonite solution were prepared respectively, and then the polyvinyl alcohol solution and the montmorillonite solution (montmorillonite particle size 0.8μm) were applied to the surface of the polyurethane sponge in sequence using a spatula. After repeating the application operation 200 times, the coated polyurethane sponge was placed in a drying oven at a temperature of 70°C and dried for 3 hours to obtain the leak-proof skeleton material.

[0061] Example 4

[0062] This embodiment provides a leak-proof skeleton material and a preparation method thereof.

[0063] The raw materials for preparing the leak-proof skeleton material are as follows: the mass fraction of polyurethane sponge is 92.2%, the mass fraction of polyvinyl alcohol is 5.2%, and the mass fraction of sepiolite is 2.6%.

[0064] A 0.9wt% polyvinyl alcohol solution and a 0.5wt% sepiolite solution were prepared respectively, and then the polyvinyl alcohol solution and the sepiolite solution (sepiolite particle size 0.8μm) were applied to the surface of the polyurethane sponge in sequence using a spatula. After repeating the application operation 200 times, the coated polyurethane sponge was placed in a drying oven at a temperature of 80°C and dried for 4 hours to obtain the leak-proof skeleton material.

[0065] Example 5

[0066] This embodiment provides a leak-proof skeleton material and a preparation method thereof.

[0067] The raw materials for preparing the leak-proof skeleton material include: the mass fraction of polyurethane sponge is 91.9%, the mass fraction of polyvinyl alcohol is 5.4%, and the mass fraction of nano calcium carbonate is 2.7%.

[0068] A 1wt% polyvinyl alcohol solution and a 0.5wt% nano-calcium carbonate solution were prepared respectively, and then the polyvinyl alcohol solution and the nano-calcium carbonate solution (the particle size of the nano-calcium carbonate was 0.5 μm) were applied to the surface of the polyurethane sponge in sequence using a spatula. After repeating the application operation 200 times, the coated polyurethane sponge was placed in a drying oven at a temperature of 80° C. and dried for 5 hours to obtain the leak-proof skeleton material.

[0069] Example 6

[0070] This embodiment provides a leak-proof skeleton material and a preparation method thereof.

[0071] The raw materials for preparing the leak-proof skeleton material are as follows: the mass fraction of polyurethane sponge is 92.2%, the mass fraction of polyvinyl alcohol is 5.2%, and the mass fraction of montmorillonite is 2.7%.

[0072] A mixed solution of 10 wt% montmorillonite and polyvinyl alcohol (the mass ratio of montmorillonite to polyvinyl alcohol is 0.8:1.5, and the particle size of montmorillonite is 0.1 μm) is prepared; then the mixed solution of montmorillonite solution and polyvinyl alcohol is applied to the surface of the polyurethane sponge using a spatula, and after repeating the application operation 200 times, the coated polyurethane sponge is placed in a drying oven at a temperature of 80°C and dried for 8 hours to obtain a leak-proof skeleton material.

[0073] Example 7

[0074] This embodiment provides a leak-proof skeleton material and a preparation method thereof.

[0075] The raw materials for preparing the leak-proof skeleton material are as follows: the mass fraction of polyurethane sponge is 93%, the mass fraction of polyvinyl alcohol is 4.4%, and the mass fraction of montmorillonite is 2.2%.

[0076] A mixed solution of 15 wt% montmorillonite and polyvinyl alcohol (the mass ratio of montmorillonite to polyvinyl alcohol is 1:2, and the particle size of montmorillonite is 0.1 μm) is prepared; then the mixed solution of montmorillonite solution and polyvinyl alcohol is applied to the surface of the polyurethane sponge using a spatula, and the application operation is repeated 120 times. The coated polyurethane sponge is placed in a drying oven at a temperature of 60°C and dried for 6 hours to obtain a leak-proof skeleton material.

[0077] Example 8

[0078] This embodiment provides a leak-proof skeleton material and a preparation method thereof.

[0079] The raw materials for preparing the leak-proof skeleton material are as follows: the mass fraction of polyurethane sponge is 92.3%, the mass fraction of polyvinyl alcohol is 4.6%, and the mass fraction of montmorillonite is 3.1%.

[0080] A mixed solution of 15 wt% montmorillonite and polyvinyl alcohol (the mass ratio of montmorillonite to polyvinyl alcohol is 1:1.5, and the particle size of montmorillonite is 0.5 μm) is prepared; then the mixed solution of montmorillonite solution and polyvinyl alcohol is applied to the surface of the polyurethane sponge using a spatula, and after repeating the application operation 50 times, the coated polyurethane sponge is placed in a drying oven at a temperature of 80°C and dried for 2 hours to obtain a leak-proof skeleton material.

[0081] Example 9

[0082] This embodiment provides a leak-proof skeleton material and a preparation method thereof.

[0083] The raw materials for preparing the leak-proof skeleton material are as follows: the mass fraction of polyurethane sponge is 92%, the mass fraction of polyvinyl alcohol is 5.2%, the mass fraction of montmorillonite is 2.6%, and the mass fraction of glutaraldehyde is 0.2%.

[0084] A mixed solution of 15 wt% montmorillonite and polyvinyl alcohol (the mass ratio of montmorillonite to polyvinyl alcohol is 1:2, and the particle size of montmorillonite is 0.5 μm) is prepared; after adding 0.8 wt% glutaraldehyde to the mixed solution, the mixed solution of montmorillonite solution and polyvinyl alcohol is applied to the surface of the polyurethane sponge with a spatula, and after repeating the application operation 200 times, the coated polyurethane sponge is placed in a drying oven at a temperature of 80°C and dried for 8 hours to obtain a leak-proof skeleton material.

[0085] Example 10

[0086] This embodiment provides a leak-proof skeleton material and a preparation method thereof.

[0087] The raw materials for preparing the leak-proof skeleton material are as follows: the mass fraction of polyurethane sponge is 91.8%, the mass fraction of polyvinyl alcohol is 5.4%, the mass fraction of montmorillonite is 2.4%, and the mass fraction of glutaraldehyde is 0.4%.

[0088] A mixed solution of 10 wt% montmorillonite and polyvinyl alcohol (the mass ratio of montmorillonite to polyvinyl alcohol is 0.8:1.8, and the particle size of montmorillonite is 0.5 μm) is prepared; after adding 1 wt% glutaraldehyde to the mixed solution, the mixed solution of montmorillonite solution and polyvinyl alcohol is applied to the surface of a polyurethane sponge using a spatula, and after repeating the application operation 50 times, the coated polyurethane sponge is placed in a drying oven at a temperature of 60°C and dried for 2 hours to obtain a leak-proof skeleton material.

[0089] Embodiment 11

[0090] This embodiment provides a leak-proof skeleton material and a preparation method thereof.

[0091] The raw materials for preparing the leak-proof skeleton material are as follows: the mass fraction of polyurethane sponge is 91.8%, the mass fraction of polyvinyl alcohol is 5.4%, the mass fraction of montmorillonite is 2.7%, and the mass fraction of boric acid is 0.1%.

[0092] A mixed solution of 15 wt% montmorillonite and polyvinyl alcohol (the mass ratio of montmorillonite to polyvinyl alcohol is 1:2, and the particle size of montmorillonite is 0.5 μm) is prepared; after adding 0.9 wt% boric acid to the mixed solution, the mixed solution of montmorillonite and polyvinyl alcohol is applied to the surface of the polyurethane sponge using a spatula, and after repeating the application operation 180 times, the coated polyurethane sponge is placed in a drying oven at a temperature of 80°C and dried for 6 hours to obtain a leak-proof skeleton material.

[0093] Example 12

[0094] This embodiment provides a leak-proof skeleton material and a preparation method thereof.

[0095] The present embodiment is different from the embodiment 1 in that a 0.5 wt % montmorillonite solution (montmorillonite particle size 1 μm) and a 1 wt % polyvinyl alcohol solution are sequentially applied to the surface of the polyurethane sponge using a spatula, and other conditions remain unchanged.

[0096] Comparative Example 1

[0097] This comparative example provides a leak-proof skeleton material.

[0098] This comparative example directly uses polyurethane sponge as the leak-proof skeleton material.

[0099] Comparative Example 2

[0100] This comparative example provides a leak-proof skeleton material and a preparation method thereof.

[0101] The raw materials for preparing the leak-proof skeleton material are as follows: the mass fraction of polyurethane sponge is 97.2%, the mass fraction of montmorillonite is 2.7%, and the mass fraction of boric acid is 0.1%.

[0102] The difference between this comparative example and Example 11 is that 15 wt % montmorillonite solution is used instead of 15 wt % mixed solution of montmorillonite and polyvinyl alcohol, and other conditions remain unchanged.

[0103] Comparative Example 3

[0104] This comparative example provides a leak-proof skeleton material and a preparation method thereof.

[0105] The raw materials for preparing the leak-proof skeleton material are as follows: the mass fraction of polyurethane sponge is 94.5%, the mass fraction of polyvinyl alcohol is 5.4%, and the mass fraction of boric acid is 0.1%.

[0106] The difference between this comparative example and Example 11 is that 15 wt % polyvinyl alcohol solution is used instead of 15 wt % mixed solution of montmorillonite and polyvinyl alcohol, and other conditions remain unchanged.

[0107] Performance evaluation and testing

[0108] 1. Temperature resistance test:

[0109] After the test material was rolled and heated in a high-temperature roller heating furnace, a high-temperature resistance evaluation experiment was carried out; the rolling heating temperature was 120°C and the rolling heating time was 16 hours.

[0110]

[0111] In the above formula, α is the mass retention rate, %; M1 is the mass of the material before hot rolling, g; M2 is the mass of the material after hot rolling, g.

[0112] Table 1

[0113] Serial number Leakage plugging skeleton materials prepared in different embodiments Quality retention rate (%) 1 Example 1 94.1 2 Example 4 92.6 3 Example 5 91.8 4 Example 7 95.6 5 Example 9 96.2 6 Embodiment 11 96.9 7 Example 12 93.5 8 Comparative Example 1 90.5 9 Comparative Example 2 90.5 10 Comparative Example 3 91.2

[0114] The results in Table 1 show that the plugging skeleton materials prepared in the embodiments of the present invention have a mass retention rate greater than that of the plugging skeleton materials prepared by the preparation methods of Comparative Examples 1-3 after high-temperature hot rolling, indicating that the plugging skeleton materials prepared in the embodiments of the present invention have good temperature resistance; further, the mass retention rate of Example 1 of the present invention is greater than that of Examples 4 and 5, indicating that the method of modifying the polyurethane sponge with montmorillonite has better temperature resistance than nano-calcium carbonate and sepiolite; the mass retention rate of Example 7 is greater than that of Example 1, indicating that the preparation method of Example 7 is more effective in improving the temperature resistance; the mass retention rates of Examples 9 and 11 are greater than those of Example 7, indicating that after adding a cross-linking agent to the mixed solution, the film-forming effect is good, and the temperature resistance of the plugging skeleton material is further improved; Example 12 exchanges the application order of the montmorillonite solution and the polyvinyl alcohol solution compared with Example 1, and the temperature resistance of the prepared plugging skeleton material is worse than that of Example 1.

[0115] 2. Oil resistance test:

[0116] The diesel temperature was heated to 100°C in an oil bath, and the test material was then added to the diesel and soaked for 16 hours. The test material was then taken out and dried, and the tensile strength was measured using a universal testing machine. The tensile strength retention rate was obtained using the following formula.

[0117]

[0118] In the above formula, β is the tensile strength retention rate, %; P1 is the tensile strength of the material before immersion, kPa; P2 is the tensile strength of the material after immersion, kPa.

[0119] Table 2

[0120] Serial number Leakage plugging skeleton materials prepared in different embodiments Tensile strength retention rate (%) 1 Example 1 81.1 2 Example 4 78.9 3 Example 5 75.8 4 Example 7 86.6 5 Example 9 89.5 6 Embodiment 11 92.4 7 Example 12 80.2 8 Comparative Example 1 38.7 9 Comparative Example 2 38.9 10 Comparative Example 3 40.3

[0121] The results in Table 2 show that after the plugging skeleton materials prepared in the embodiments of the present invention are immersed in diesel, their tensile strength retention rates are greater than those of the plugging skeleton materials prepared by the preparation methods of Comparative Examples 1-3, indicating that the plugging skeleton materials prepared in the embodiments of the present invention have excellent oil resistance; the tensile strength retention rate of Example 1 is greater than that of Examples 4 and 5, indicating that the method of modifying the polyurethane sponge using montmorillonite has a better oil resistance effect than nano-calcium carbonate and sepiolite; the tensile strength retention rate of Example 7 is greater than that of Example 1, indicating that the preparation method of Example 7 is more effective in improving the oil resistance; the tensile strength retention rates of Examples 9 and 11 are greater than that of Example 7, indicating that after adding a cross-linking agent to the mixed solution, the film-forming effect is good, and the oil resistance of the plugging skeleton material is further improved; Compared with Example 1, Example 12 exchanges the application order of the montmorillonite solution and the polyvinyl alcohol solution, and the oil resistance of the prepared plugging skeleton material is slightly worse than that of Example 1.

[0122] 3. Mechanical properties test

[0123] Referring to the national industry standard GB / T6344-2008 "Determination of tensile strength and elongation at break of soft foam polymer materials", the tensile strength of the elastic mesh plugging skeleton material is tested.

[0124] Table 3

[0125] Serial number Leakage plugging skeleton materials prepared in different embodiments Tensile strength(MPa) 1 Example 1 1.23 2 Example 4 0.81 3 Example 5 0.59 4 Example 7 2.92 5 Example 9 3.31 6 Embodiment 11 5.56 7 Example 12 1.14 8 Comparative Example 1 0.17 9 Comparative Example 2 0.17 10 Comparative Example 3 0.19

[0126] The results in Table 3 show that the tensile strength of the plugging skeleton materials prepared in the embodiments of the present invention is greater than that of the plugging skeleton materials prepared by the preparation methods of Comparative Examples 1-3, indicating that the plugging skeleton materials prepared in the embodiments of the present invention have good mechanical properties; the tensile strength of Example 1 is greater than that of Examples 4 and 5, indicating that the method of modifying the polyurethane sponge using montmorillonite has a better film-forming effect than nano-calcium carbonate and sepiolite, thereby giving the plugging skeleton material better mechanical properties; the tensile strength of Example 7 is greater than that of Example 1, indicating that the preparation method of Example 7 is more effective in improving the mechanical properties; the tensile strength of Examples 9 and 11 is greater than that of Example 7, indicating that after adding a cross-linking agent to the mixed solution, the film-forming effect is better and the mechanical properties are more excellent; Compared with Example 12, the application order of the montmorillonite solution and the polyvinyl alcohol solution is exchanged in Example 1, and the tensile strength of the prepared plugging skeleton material does not change significantly, indicating that the selection of the raw material for coating the first layer has little effect on the overall performance of the composite membrane.

[0127] 4. Leakage plugging performance test

[0128] The plugging performance of the plugging skeleton materials prepared in the examples of the present invention and the comparative examples was evaluated to test the effects of the dispersibility and mechanical strength of the plugging skeleton materials on the plugging performance.

[0129] An evaluation experiment was carried out using a wedge-shaped long crack plugging experimental device. The plugging evaluation test results are shown in the table below.

[0130] The basic formula of the plugging liquid is composed of white oil, sawdust and ultrafine calcium carbonate, wherein the amount of sawdust added is 3wt% and the amount of ultrafine calcium carbonate added is 3wt% based on the weight of the white oil; the plugging skeleton materials prepared in different embodiments are added to the basic formula of the plugging liquid, and the added amount is 5wt% of the white oil.

[0131] Table 4

[0132]

[0133] The results in Table 4 show that the plugging effect of adding the plugging skeleton material prepared in the embodiment of the present invention to the basic formula of the plugging liquid is significantly better than that of adding the plugging skeleton material prepared in Comparative Examples 1-3, so that the crack plugging area moves forward, the pressure bearing capacity of the plugging layer is significantly increased, and the crack leakage is reduced; compared with Examples 4 and 5, the crack plugging area in Example 1 moves forward and the crack leakage is reduced, indicating that the method of modifying the polyurethane sponge with montmorillonite has a better film-forming effect than nano-calcium carbonate and sepiolite, thereby giving the plugging skeleton material better dispersibility and plugging performance; compared with Example 7, Example 8 has a better performance than Example 9. In Example 1, the crack plugging area moves forward and the crack leakage is reduced, indicating that the film-forming performance of the preparation method of Example 7 is better; in Examples 9 and 11, which are greater than Example 7, the crack plugging area moves forward, the pressure bearing capacity of the plugging layer is significantly increased, and the crack leakage is reduced, indicating that after adding a cross-linking agent to the mixed solution, the film-forming effect is better and the plugging performance is improved; in Example 1, compared with Example 12, the application order of the montmorillonite solution and the polyvinyl alcohol solution is swapped, and the plugging performance of the prepared plugging skeleton material does not change significantly, indicating that the choice of the raw material for coating the first layer has little effect on the overall performance of the composite membrane.

[0134] 5. Contact angle measurement of composite films formed by layer-by-layer self-assembly of polyvinyl alcohol and montmorillonite on the surface of polyurethane sponge

[0135] The hydrophobicity of the leak-proof skeleton material (polyurethane sponge surface containing a composite film) prepared in Example 11 of the present invention was tested and evaluated by using the contact angle measurement method;

[0136] According to the preparation method of the leak-proof skeleton material of the present invention, a composite film is formed on the surface of the skeleton material polyurethane sponge with a relatively flat surface, and the contact angle of a water drop on the surface of the leak-proof skeleton material is measured using a contact angle meter; the specific results are shown in the attached Figure 1 .

[0137] from Figure 1 It can be seen that the contact angle is 131°, and the surface of the plugging skeleton material is obviously hydrophobic.

[0138] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.

Claims

1. A leak-proof skeleton material, It is characterized in that The plugging skeleton material comprises an elastic material and a deposited film coated on the surface of the elastic material; the raw materials for preparing the deposited film comprise polyvinyl alcohol, inorganic particles and an optional cross-linking agent; the elastic material is selected from at least one of sponge, elastic graphite and rubber.

2. The leak-proof skeleton material according to claim 1, It is characterized in that Based on the total mass of the leak-proof skeleton material, The mass percentage of elastic material is 89% to 95.7%. The mass percentage of polyvinyl alcohol is 2.2% to 5.6%; The mass percentage of inorganic particles is 2.1% to 4.4%; The mass percentage of the cross-linking agent is 0% to 1%.

3. The leak-proof skeleton material according to claim 1 or 2, It is characterized in that The average particle size of the inorganic particles is 0.05 μm to 1 μm; preferably, the inorganic particles are selected from at least one of montmorillonite, nano calcium carbonate and sepiolite; And / or, the average particle size of the elastic material is 1 mm to 5 mm; And / or, the sponge is selected from polyurethane sponge or polyether polyol sponge; And / or, the sponge has a pore size of 10ppi to 40ppi, an open porosity of 95% to 96%, and a density of 21kg / cm 3 ~22kg / cm 3 .

4. The leak-proof skeleton material according to any one of claims 1 to 3, It is characterized in that The cross-linking agent is selected from at least one of glutaraldehyde and boric acid.

5. The leak-proof skeleton material according to any one of claims 1 to 4, It is characterized in that The mass retention rate of the leak-proof skeleton material is 91.8% to 96.9%, the tensile strength is 0.59 MPa to 5.56 MPa, and the tensile strength retention rate is 75.8% to 92.4%.

6. The method for preparing the leak-proof skeleton material according to any one of claims 1 to 5, It is characterized in that The steps include: 1) coating a solution I containing polyvinyl alcohol and a solution II containing inorganic particles on the surface of the elastic material in sequence, or coating a mixed solution containing inorganic particles and polyvinyl alcohol on the surface of the elastic material; 2) After repeating step 1) for 50 to 200 times, the coated elastic material is dried to obtain the leak-proof skeleton material.

7. The preparation method according to claim 6, It is characterized in that In step 1), in the solution I containing polyvinyl alcohol, the solvent I is selected from water; preferably, the content of polyvinyl alcohol in the solution I containing polyvinyl alcohol is 0.5wt% to 1.0wt%; And / or, in step 1), in the solution II containing inorganic particles, the solvent II is selected from at least one of water, white oil and brine; preferably, the brine is selected from a NaCl aqueous solution with a mass concentration of 20%; And / or, the content of inorganic particles in the solution II containing inorganic particles is 0.1wt% to 0.5wt%; And / or, in step 2), the drying conditions include: temperature of 60° C. to 80° C., and time of 2 h to 8 h.

8. The preparation method according to claim 6 or 7, It is characterized in that In step 1), the mixed solution containing inorganic particles and polyvinyl alcohol is a mixed solution of solution I containing polyvinyl alcohol and solution II containing inorganic particles, wherein the total content of the inorganic particles and polyvinyl alcohol is 10wt% to 15wt%; And / or, the mass ratio of the inorganic particles to the polyvinyl alcohol in the mixed solution containing the inorganic particles and polyvinyl alcohol is (0.7-1):(1.5-2).

9. The preparation method according to any one of claims 6 to 8, It is characterized in that In step 1), the mixed solution containing inorganic particles and polyvinyl alcohol also includes a cross-linking agent; And / or, the content of the cross-linking agent in the mixed solution containing the inorganic particles and polyvinyl alcohol is 0.1wt% to 1wt%.

10. Use of the plugging skeleton material according to any one of claims 1 to 5 or the plugging skeleton material prepared by the preparation method according to any one of claims 6 to 9 in plugging in drilling engineering, plugging water in oil production and profile control, and drilling fracturing.

Citation Information

Patent Citations

  • Fractured stratum high-elasticity high-temperature-resistance plugging agent for drilling fluid and preparation method of plugging agent

    CN109796943A

  • High-elasticity rapid plugging agent and preparation method

    CN111944502A

  • Plugging agent containing modified elastic framework material

    CN114250065A